Arts and Health: A New Paradigm - Moss, Hilary (Voices: A World Forum for Music Therapy, 2016)
This position paper presents a new paradigm about the intrinsic structure and nature of arts and health practice. This paradigm is based on a variety of research experiences over twenty years working as a music therapist, musician, music and health practitioner, researcher and director of an arts and health programme in university teaching hospitals, community contexts, and non-governmental organizations in Ireland and the UK. The aim of this paper is to propose a new perspective on the term arts and health, to encompass all arts related activity that exists in contexts related to health. This paradigm aims to counter the artificial and defensive barriers constructed between practitioners and professional groups within the field, encourage greater respect and understanding between practitioners and assist in identifying training and development needs for the various arts professionals working in contexts related to health and well-being. It is proposed that the current commonly held assumptions surrounding definitions of arts and health and arts therapies are unhelpful and problematic and should be refined.